Placement of a Catheter into the Transverse Sinus in Monitoring Intracranial Lesions: A Technical Note - Dai, Xingping; Chen, Yanyi; Xia, Mingyue; Yi, Min; Xu, Xia; Wang, Dongsheng; Nemoto, Edwin M. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
High intracranial pressure (ICP) can be induced by stroke, brain trauma, and brain tumor, and lead to cerebral injury. Monitoring the blood flow of a damaged brain is important for detecting intracranial lesions. Blood sampling is a better way to monitor changes in brain oxygen and blood flow than computed tomography perfusion and magnetic resonance imaging. This article describes how to take blood samples from the transverse sinus in a high ICP rat model. Also, it compares the blood samples from the transverse sinus and femoral artery/vein through blood gas analysis and neuronal cell staining. The findings may be of significance to the monitoring of the oxygen and blood flow of intracranial lesions.
Keywords: transverse sinus; catheterization; intracranial lesions; intracranial pressure